2005
DOI: 10.1097/01.mib.0000160804.52072.6a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Role of Interleukin-15 in Crohnʼs Disease

Abstract: Our results suggest a possible anti-inflammatory role for IL-15 in CD. We postulate that its overexpression in CD potentially represents a protective mechanism against the exaggerated T(H)1 immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
(111 reference statements)
2
15
0
Order By: Relevance
“…In this approximation, we tested a combination of phorbol 12-myristate 13-acetate and ionomycin (PMA/IO). PMA/IO exposure is a commonly used procedure for the activation of T cells and for the simulation of inflammatory conditions in human colonic explants, since PMA/IO act as potent inducers of T h 1-type cytokines IL-2 and IFN-c, which are found upregulated in inflammatory bowel diseases (Niedel et al 1983;Silva et al 2005). The analysis of the data in our experiments confirmed that PMA/IO provoked an inflammation-like pattern.…”
Section: Discussionsupporting
confidence: 78%
“…In this approximation, we tested a combination of phorbol 12-myristate 13-acetate and ionomycin (PMA/IO). PMA/IO exposure is a commonly used procedure for the activation of T cells and for the simulation of inflammatory conditions in human colonic explants, since PMA/IO act as potent inducers of T h 1-type cytokines IL-2 and IFN-c, which are found upregulated in inflammatory bowel diseases (Niedel et al 1983;Silva et al 2005). The analysis of the data in our experiments confirmed that PMA/IO provoked an inflammation-like pattern.…”
Section: Discussionsupporting
confidence: 78%
“…Such a tight negative regulation may serve to avoid deleterious consequences of excessive NK cell activation. Tight control of IL-15R␣ may be particularly important in humans who can show detectable levels of circulating IL-15, particularly in cases of inflammation and autoimmune pathologies (51,52). This contrasts with murine models where IL-15 remains mostly undetectable in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…During the acute phase of the disease, CD4 ϩ T cells are the primary source of host IFN-␥ production (48), leading to immunopathology and ultimate death of the animal (11,26). CD4 ϩ T cells are known to play a primary role in number of autoimmune diseases such as inflammatory bowel disease, Crohn's disease, and experimental autoimmune encephalomyelitis (49)(50)(51). However, the importance of IL-15 in the elicitation of primary CD4 ϩ T cell response and subsequent effect on the pathogenesis of these diseases has not been reported.…”
Section: Discussionmentioning
confidence: 99%